Modal Sosial Model Komunikasi Partisipatif Sebagai Modal Sosial dalam Pembangunan Pedesaan (Studi Kasus Desa Noeltoko, Kecamatan Miomaffo Barat, Kabupaten TTU) - Ody Wolfrit Matoneng; Marsianus Falo (AGRIMOR, 2022)
The concept of rural development is essentially based on communication and participation to achieve a consensus. Rural development is based on rural communities who are willing to be empowered through the order of social capital values. Noeltoko Village is known as a village which has local values and historical values that are maintained in TTU Regency. However, with the development of the times, the social activities that have become traditions and cultures have slowly begun to fade. The problem faced by the people of Noeltoko Village is the decline in social capital including social trusts, social norms, and social networks, which are decreasing caused by the decline in participatory communication traditions. Convergent or centralized communication as the basis of research aimed to improve the tradition of participatory communication into social capital from the empowerment of the people of Noeltoko Village. This research was expected to generate a participatory communication model through the convergence of communication that is able to influence social capital in Noeltoko Village. The research was designed into mix methods research. The purposive technique was used in determining the location. The determination of population and samples using the rule of thumb technique where a sample of less than 1,000 is required to sample a minimum of 30% of the total population, namely 42 samples obtained by 30% of the 164 heads of families. The data collection method consisted of primary data obtained from samples and secondary data obtained from complementary sources such as literature reviews. Data analysis techniques used descriptive statistical analysis as well as inferential statistical analysis using path analysis through Partial Least Square (PLS) software. The results of this study showed that social capital will increase if it was conditioned by the empowerment of convergent communication through indicators of dialogue level, level of interaction, and level of participation.